Advances in Communication Technology : Teleconferencing and Telepresence - Kumar, Ashok (DESIDOC Journal of Library & Information Technology, 2002)
Technology is developing at a very fast rate and what looked impossible a few years back is becoming reality now. Sometimes a possibility may look to be impractical because it goes against our accustomed style of working or is unacceptable because it does not offer a complete solution. However,people are getting used to the existence of new technologies. Already people have started using voice and electronic mail as preferred forms of communication in the same way as the use of remotely driven devices. http://dx.doi.org/10.14429/dbit.13.5.3083